The human right to resist in international and constitutional law - Murphy, Shannonbrooke (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2025)
""This is an indispensable book for understanding the concept of the human right to resist and its status in international and constitutional law. It will be a valuable resource for academics or students researching the 'right to resist' and activists or practitioners making, assessing or defending claims or adjudicators evaluating defences. ""--
Introduction : in from the margins -- Advancing a legal definition of the right -- Clarifying the nature and legal function of the right -- Identifying the elements and legal content of the right -- Domestic provision in constitutional law -- Recognition in general or customary international law -- Provision in treaty law and other international codification -- Conclusions and an agenda for reconsideration.
BIBINDX
Keywords: International law and human rights; Human rights; Constitutional law